A STUDY ON COLLEGE STUDENTS' WRITING COMPETENCE - Meilina Haris Mayekti (Journal of Applied Linguistics (ALTICS), 2020)
AbstractThis research attempts to find out the writing competence of college students, detect the cause of the problems and propose some suggestion to deal with the problem. The population of this research is the second Semester students of English Education Department UNU Purwokerto. Since the number of population is less than 100 students the writer took them all as sample. It means that the number of sample is the same as the number of the population that is 39 students. The method of this research was descriptive. This research was conducted on May 2018. The instrument used in this research is a test. The computation of the data to find out writing competence uses percentage formula. After the data has been analysed, the data showed that the writing competence is 62.64%, it means that the writing competence of the second semester students of English Education Department UNU Purwokerto is good. The most problems of the students are grammatical. Those are the pattern of tenses, addition, and misformation.Key words: writing, competence, descriptive, college students, grammatical problems